Effect of mouth rinses on roughness and optical properties of restorative materials for oral rehabilitation - de Carvalho, Laura Firmo; Bergamo, Edmara T. P.; Benalcázar-Jalkh, Ernesto B.; Campos, Tiago M. B.; Zahoui, Abbas; Fermino, Elisa de Souza; de Oliveira, Ana Clara Mota; Magalhães, Ana Carolina; Bonfante, Estevam A.; Bezerra, Fábio José B. [UNESP]; Alves, Larissa M. M. (MJS Publishing, Medical Journals Sweden AB, 2025)
The objective of this study was to evaluate the influence of mouth rinses on the roughness and optical properties of three polymeric restorative materials. Cylinders were obtained from Ivotion Dent, Ivotion Base, and Empress Direct. Nano-hybrid composite teeth were also investigated (SR Phonares II). Specimens were divided into four subgroups for mouth rinsing simulation according to the mouth rinse: (1) Distilled water; (2) Soft-Tissue; (3) Implants/Cosmetic; and (4) PerioGard. Roughness (Ra) and optical properties were evaluated before and at timepoints during mouth rinsing simulation. Roughness increased after rinsing simulation for Ivotion Dent and Ivotion Base after all mouth rinses. Soft-Tissue and Cosmetic increased the Ra of Empress Direct. Translucency parameter (TP) of Ivotion Dent and Empress Direct increased, while Contrast ratio (CR) values decreased after rinsing simulation, regardless of the solution used. Ivotion Base demonstrated higher TP after rinsing with Soft-Tissue and Implants mouth rinses compared to the control group, while no difference among them was observed for CR. The mouth rinses affected the roughness and optical properties of materials differently after the rinsing simulation.
Keywords: acrylic resin; CAD-CAM; mouth rinse; roughness; translucency